If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 8) = 182 Reorder the terms: 7(8 + 3x) = 182 (8 * 7 + 3x * 7) = 182 (56 + 21x) = 182 Solving 56 + 21x = 182 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 21x = 182 + -56 Combine like terms: 56 + -56 = 0 0 + 21x = 182 + -56 21x = 182 + -56 Combine like terms: 182 + -56 = 126 21x = 126 Divide each side by '21'. x = 6 Simplifying x = 6
| 5(3x+5)=3(5x+10) | | x^2-4xy=3y^3 | | 2x^2-16+3x^2=180 | | -22+20+2+(-18)= | | 2v/3=24 | | 5e^9x=9 | | 5e^9*x=9 | | -5x-10=-7x+6 | | 4-6x=4+6x | | 10x+2=4(2x-3) | | 8m-2=-3 | | 2.5(10x+8)+3x= | | 10x-2=4(2x-3) | | 2n*n-5=3n*n^2*n*4 | | 4x^3+5x^2-18x+9=0 | | 3.5x+215=495 | | 30/y=6/1/5 | | 2(3x-7)-10=20 | | -4x-118=116+9x | | 21+x=-39 | | 2[7-5(1-x)]+6x=-12+3[6(x+1)-3x] | | -3.7t-4.1=6.3t+6 | | 21+x=-31 | | 3x+100=4x+x | | X+3=y-5 | | (x+7)+(2x-1)+(2x+3)=79 | | 3n+n+5=37 | | (12y+9x)-(x-y)= | | -3(5s-6)-18=-3(7s+2)-3 | | 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 |